A novel conceptual model of heart rate autonomic modulation based on a small-world modular structure of the sinoatrial node - Maltsev, Alexander V.; Stern, Michael D.; Lakatta, Edward G.; Maltsev, Victor A. (Frontiers in Physiology, 2023)
The present view on heartbeat initiation is that a primary pacemaker cell or a group of cells in the sinoatrial node (SAN) center paces the rest of SAN and the atria. Recent high-resolution imaging studies show, however, a more complex paradigm of SAN function that emerges from heterogeneous signaling, mimicking brain cytoarchitecture and function. Here we developed and tested a new conceptual numerical model of SAN organized similar to brain networks featuring modular structure with small-world topology. In our model, a lower rate module leads AP firing in the basal state and during parasympathetic stimulation, whereas a higher rate module leads during β-adrenergic stimulation. Such system reproduces the respective shift of the leading pacemaker site observed experimentally and a wide range of rate modulation and robust function whilst conserving energy. Since experimental studies found functional modules at different scales, from a few cells up to the highest scale of superior and inferior SAN, the SAN appears to feature hierarchical modularity, i.e. within each module there is a set of sub-modules, like in brain exhibiting greater robustness, adaptivity, and evolvability of network function. In perspective, our model offers a new mainframe to interpret new data of heterogenous signaling in SAN at different scales, providing new insights into cardiac pacemaker function and SAN-related cardiac arrhythmias in aging and disease.